Mixing due to a heated elliptic air jet - Zhang, Kenny Zhenkuan (2013)
This paper presents measurements of velocity and temperature for a contoured contraction nozzle elliptic air jet with a 2:1 aspect ratio issuing into stagnant unconfined surroundings. Initial conditions at the jet nozzle exit plane were laminar. All measurements of mean and root-mean-square (RMS) velocities and temperatures were carried out using hot-wire and cold-wire anemometers. Flow development was found to be more rapid in the minor axis than major axis due to the thinner initial boundary layer momentum thickness in the minor axis plane. This is clearly demonstrated by the rapid growth of the jet width in the minor axis (compared to the major axis) in the near-field of the jet. Self-similarity in the mean velocity and temperature profiles was attained relatively early. However, RMS quantities have not become self-similar even by the streamwise distance of 38 equivalent jet nozzle diameters (De). One axis-switchover due to the initial difference in jet-width growth rates in the two axes was detected in the current jet. The rates of centerline temperature decay, temperature half-width growths and peak RMS temperatures at all measurement locations were consistently higher than their velocity counterparts. The temperature spreading rate in the major axis was found to be significantly larger vis-à-vis that of velocity, possibly due to the minima in radius of curvature of the elliptic geometry. All the results presented suggest that the use of heated elliptic jets could offer enhanced mixing performance in relevant applications.